Making Simple Calculator Programming Using Java Language - Azzam, Muhammad Musyaffa (Journal Collabits, 2025)
This research aims to develop a simple calculator application using Java Socket-based client-server connection. The research methodology involves the process of application development and functional testing of the calculator. The application allows users to perform basic mathematical operations such as addition, subtraction, multiplication, and division. The implementation using Java Socket enables communication between the client and server, allowing users to send operation requests to the server and receive the results back. The testing results show that the application functions well and is capable of producing accurate results. This journal can serve as a reference for developers interested in creating a simple calculator application using the Java programming language.